Pengaruh Wudhu Sebelum Tidur Terhadap Kualitas Tidur Pasien Hipertensi di RSUD Dr. Chasbullah Abdulmadjid Kota Bekasi - Selvi Monika; Fitrian Rayasari; Siti Badriah (FORIKES, 2021)
Hypertension is a condition where a person has an increase in blood pressure above normal caused by various conditions. Not all hypertension sufferers have difficulty sleeping, but in general patients who are hospitalized have difficulty sleeping, due to other factors. If the sleep quality of a hypertensive patient is disturbed, it can cause an increased pacemaker which is at risk of complications. Wudu is one of the alternatives for hypertensive patients who experience sleep quality disturbances. Wudu is a part of therapy that can affect the neurological system because it has benefits in providing a cold sensation, giving a sense of calm or relaxation. The purpose of this study was to determine the effect of ablution on sleep quality in hypertensive patients who were hospitalized, after performing ablution therapy before going to bed at dr. Chasbullah Abdul Madjid Bekasi City. The type of this study was quasi experiment with pre and post group design. The sample in this study were hypertensive patients who were treated at least one night in dr. Chasbullah Abdulmadjid Bekasi City, with a sample size of 17 interventions and 17 controls. Data analysis was bivariate using non-parametric tests. The p-value of hypothesis testing was 0.0001 (